2013
DOI: 10.1007/s10764-013-9678-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climatic Factors on the Activity Budgets of Barbary Macaques (Macaca sylvanus)

Abstract: Climatic conditions can significantly affect the behaviour of animals and constrain their activity or geographic distribution. The Barbary macaque (Macaca sylvanus) is one of the few primates that live outside the tropics. Here we analyse if and how the activity budgets of the Barbary macaque are affected by climatic variables (i.e. air temperature, relative humidity, rainfall, and snow coverage). We collected scan sampling data, over a period of almost three years, on the activity budgets of four groups of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 40 publications
1
59
0
1
Order By: Relevance
“…For example, geladas (Theropithecus gelada) increase the time spent feeding at low temperature and decreased habitat quality, due to increasing thermal requirements (Iwamoto and Dunbar 1983). A similar, negative relationship between temperature and time spent feeding has been found in Barbary macaques (Macaca sylvanus, Majolo et al 2013) and Yunnan snub-nosed monkeys (Grueter et al 2013). In contrast, Japanese macaques (M. fuscata) decrease traveling and feeding time to save energy when temperatures are low and the thermoregulatory cost is severe (Hanya 2004).…”
Section: Introductionsupporting
confidence: 57%
“…For example, geladas (Theropithecus gelada) increase the time spent feeding at low temperature and decreased habitat quality, due to increasing thermal requirements (Iwamoto and Dunbar 1983). A similar, negative relationship between temperature and time spent feeding has been found in Barbary macaques (Macaca sylvanus, Majolo et al 2013) and Yunnan snub-nosed monkeys (Grueter et al 2013). In contrast, Japanese macaques (M. fuscata) decrease traveling and feeding time to save energy when temperatures are low and the thermoregulatory cost is severe (Hanya 2004).…”
Section: Introductionsupporting
confidence: 57%
“…Nevertheless, our findings provide new insights into the adaptations of our study species to its challenging environment. Across the whole study period and in both the mating and non-mating seasons, T3 levels were negatively related to foraging time, an inverse measure of food availability [10]. Moreover, T3 levels across the whole study were lower in the wild-feeding group.…”
Section: Discussionmentioning
confidence: 90%
“…We do know that, at high temperatures, some studies have revealed that animals tend to spend more time resting (Stelzner, 1988;Hill, 2006;Campos and Fedigan, 2009;Korstjens et al, 2010;Sato, 2012;Majolo et al, 2013), and that resting and shade-seeking are critical for thermoregulation (e.g., Campos and Fedigan, 2009): high heat load can cause severe dehydration and potentially fatal hyperthermia (Taylor, 1970). In contrast to the reduced demand for shade-seeking and resting in colder temperatures, the energetic demands of thermoregulation and digestion are higher in cold conditions (Satinoff, 2011), meaning more time needs to be spent feeding (Satinoff, 2011;Majolo et al, 2013).…”
mentioning
confidence: 99%